The Association between Stress and Children's Weight Status: A School-Based, Epidemiological Study - Aikaterini Kanellopoulou; Christina Vassou; Ekaterina N. Kornilaki; Venetia Notara; George Antonogeorgos; Andrea Paola Rojas-Gil; Areti Lagiou; Mary Yannakoulia; Demosthenes B. Panagiotakos (MDPI AG, 2022)
Given the evidence on how stress affects weight status in children, this research examined this association among Greek students aged 10-12 years old. Overall, 1452 children and their parents from several urban areas participated in an observational study conducted during the period 2014-2016. Participants completed validated questionnaires. International Obesity Task Force guidelines were used for children's weight status classification. Descriptive statistics and nested logistic regression models were used. Multivariate correspondence analysis was also used to construct a score to evaluate the children's stress levels. The overall prevalence of overweight/obesity was 27%. More than 80% of the children appeared to have a medium or high level of stress, mainly due to the school environment. School-related stress increased the odds of obesity in children. The association between stress and overweight/obesity status showed a consistent trend (adjusted odds ratios varied from 1.44 to 1.52, p-values < 0.01). Children's weight status was associated with several school-related stressors. Although the school environment may play an aggravating role in the weight status of children, family plays a catalyst role in this direction. Therefore, actions have to be promoted in the school community so that children become more health literate on a public health level.